Tipologi Kepribadian Bob A. Sitorus dalam Kumpulan Puisi Haru Hara: Kajian Psikoanalisis Carl Gustav Jung - Kuansah, Hidayat Apri (Medan Resource Center, 2024)
This research aims to determine the personality of Bob A. Sitorus and the factors influencing his personality in the poetry collection